ANÁLISE DO PROCESSO DE IMPLANTAÇÃO DA ISO 9001:2015 EM CONSTRUTORAS GOIANAS - Amaral, Tatiana; Carmo, Hanaelly Garcia; Alves, Antônio Carlos Chagas (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The ISO 9001was revised in 2015. One of the principal changes includes management of risk, which will generate changes in business process management. In view of this need, the objective of this work is to understand the behavior of construction companies of Goiás regarding the migration from ISO 9001: 2008 to the 2015 version. The research method is classified as qualitative and was carried out through studies of multiple cases. As a result, it is observed that companies are adapting to the requirements of documentary and management adjustments and, most of them state that risk management has not yet been worked out in the company.